Selecting fruit quality characteristics to predict optimum harvest time of red pitaya (Hylocereus Polyrgizus) fruit. - Melly Novita; Ahmad, Siti Hajar; Ding, Phebe (2007)
This study was carried out to predict optimal harvest time of red pitaya (hylocereus polyhizus) fruit using selected fruit physical and eating quality characteristics. Pitaya fruits were harvested at 5-day interval beginning from 25 to 40 days after anthesis (DAA) and the fruit characteristics were measured. The growing degree days (GDD) were calculated from 5 to 40 DAA. Regression analysis was carried out to study the relationship between fruit characteristics and GDD. The correlation between selected peel and pulp,L*,C*,h⁰,firmness, sugar/acid ratio and flavour were determined for fruits at 483 to 765 GDD. Characteristics that were significantly correlated were used in a forward multiple regression analysis to develop a model to predict optimal harvest time.There were significant relationship between GDD and peel L*,C*,h⁰ with R²=0.90,0.95,0.93, respectively. There were also significant relationship between GDD and pulp *,C*,h⁰ with R²=0.95,0.76,0.92 respectively. Significant positive relationship were also obtained between GDD and sugar/acid ratio (R²=0.92) and flavour (R²=0.97), while significant negative relationship (R²=0.98) occured between GDD and firmness. There were significant correlations between peel L*,C*,h⁰, pulp L* and h⁰. There were also significant correlations between firmness and both peel and pulp L*,C*,h⁰. Sugar/acid ratio was negatively correlated with peel L*, peel h⁰, pulp L* and firmness and positively correlated with peel C*, pulp h⁰ and flavour. Flavour was positively analysis showed 50%and 35% of the variability in sugar/acid ratio was accounted for by peel L* and firmness, respectively (Sugar/acid ratio=480.97 - 8.16 (Peel L*) - 39.57 (Firmness)). The peel C* and firmness accounted for 38% and 35% respectively of the variability in flavour of red pitaya (Flavour = 1.58 - 0.01 (Peel C*) - 0.16 (Firmness). The peel C* and h⁰ accounted for 45% and 51% of the variability in firmness (Firmness = 5.83 - 0.10 (Peel C*) + 0.05 (Peel h⁰). These results suggest that peel C* and h⁰ could be used to predict optimal harvest time of red pitaya.